EXTRACTION OF HYALURONIC ACID FROM ALOE BARBADENSIS (ALOE VERA) - Putri, Runita Rizkiyanti; Nugraha, Tutun; Christy, Stephanie (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2020)
Hyaluronic acid have a high moisture preservation and biocompatibility characteristic, thus allowing various usage of this substance in pharmaceutical, medicinal, and skin care products. Present manufacturing process of hyaluronic acid requires extraction of animal cells or through other methods utilizing bacteria. The aim of this research is to investigate an alternative source of hyaluronic acid extraction using plant based which is aloe vera (A. Barbadensis).  Three main parts of aloe vera (rind, mesophyll and gel) underwent several steps of extraction process and the result was compared to the sample of hyaluronic acid from goat brain. The evaluation including comparison of total carbohydrates, reducing sugars and degradation using heat treatment. The results of extraction were analyzed using UV-Spectrophotometer at 230 nm and compare to the extraction result of goat brain to ensure the presence of hyaluronic acid. It was found out that the rind part of aloe vera have the highest potential of high content of hyaluronic acid.